Sexual Deviance : Theory, Assessment, and Treatment. - Laws, D. Richard (Guilford Publications, 2008)
Now in a fully revised and updated second edition, this important work provides authoritative scientific and applied perspectives on the full range of paraphilias and other sexual behavior problems. For each major clinical syndrome, a chapter on psychopathology and theory is followed by a chapter on assessment and treatment. Challenges in working with sex offenders are considered in depth. Thoroughly rewritten to reflect a decade of advances in the field, the second edition features many new chapters and new authors. New topics include an integrated etiological model, sexual deviance across th.